Security in Smart Cities: Models, Applications, and Challenges - Hassanien, Aboul Ella.; Elhoseny, Mohamed; Ahmed, Syed Hassan; Singh, Amit Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers an essential guide to IoT Security, Smart Cities, IoT Applications, etc. In addition, it presents a structured introduction to the subject of destination marketing and an exhaustive review on the challenges of information security in smart and intelligent applications, especially for IoT and big data contexts. Highlighting the latest research on security in smart cities, it addresses essential models, applications, and challenges. Written in plain and straightforward language, the book offers a self-contained resource for readers with no prior background in the field. Primarily intended for students in Information Security and IoT applications (including smart cities systems and data heterogeneity), it will also greatly benefit academic researchers, IT professionals, policymakers and legislators. It is well suited as a reference book for both undergraduate and graduate courses on information security approaches, the Internet of Things, andreal-world intelligent applications. .
Part I: Challenges of Smart Healthcare Applications -- Big Data challenges and opportunities in IoT Applications: Health Informatics and Smart Hospitals -- Healthcare Analysis in Smart Big Data Analytics :Reviews, Challenges and Recommendations -- Realization of IoT adaptive Data hiding system for Electronic Patient Record, Embedding in Medical Images -- A Swarm Intelligence Model for Enhancing Health Care Services in Internet of Things based Applications -- A Machine Learning Model for Predicting of Chronic Kidney Disease for Internet of Things and cloud computing Applications -- Part II: Secure Models for Smart Cities Applications -- Data Security Challenges in Smart cities -- Engineering Large Complex Critical Infrastructures of Future Smart Cities for IoT applications as Self-Adaptive Systems- Security challenges in IoT Cyber world -- Blockchains for Smart Cities: A Survey -- A Review of Existing 4-bit Crypto S-box cryptanalysis Techniques and Two New Techniques with 4-bit Boolean Functions for Cryptanalysis of 4-bit Crypto S-boxes towards a Secure Internet of Things based Application -- Part III: Secure Network Communication in Smart Cities Applications -- A Robust Watermarking Scheme Using Machine Learning Transmitted Over High-Speed Net-work for Internet of Things Applications -- 4, 8, 32, 64 bit Substitution Box generation using Irreducible or Reducible Polynomials over Galois Field GF(pq) -- Local Binary Patterns for Facial Expression Recognition for Efficient Smart Applications -- Efficient Generation of Association Rules from Numeric Data using Genetic Algorithm for Smart Cities Applications -- Online User Authentication System based on Finger Knuckle Print using Smartphones.
Keywords: Computational intelligence; Artificial intelligence; Sociology, Urban; Data protection; Computational Intelligence; Artificial Intelligence; Urban Sociology; Data and Information Security